Bioethics-CSR Divide - Caio Caesar Dib (Voices in Bioethics, 2024)
Photo by Sean Pollock on Unsplash ABSTRACT Bioethics and Corporate Social Responsibility (CSR) were born out of similar concerns, such as the reaction to scandal and the restraint of irresponsible actions by individuals and organizations. However, these fields of knowledge are seldom explored together. This article attempts to explain the motives behind the gap between bioethics and CSR, while arguing that their shared agenda – combined with their contrasting principles and goals – suggests there is potential for fruitful dialogue that enables the actualization of bioethical agendas and provides a direction for CSR in health-related organizations. INTRODUCTION Bioethics and Corporate Social Responsibility (CSR) seem to be cut from the same cloth: the concern for human rights and the response to scandal. Both are tools for the governance of organizations, shaping how power flows and decisions are made. They have taken the shape of specialized committees, means of stakeholder inclusion at deliberative forums, compliance programs, and internal processes. It should be surprising, then, that these two fields of study and practice have developed separately, only recently re-approaching one another. There have been displays of this reconnection both in academic and corporate spaces, with bioethics surfacing as part of the discourse of CSR and compliance initiatives. However, this is still a relatively timid effort. Even though the bioethics-CSR divide presents mostly reasonable explanations for this difficult relationship between the disciplines, current proposals suggest there is much to be gained from a stronger relationship between them. This article explores the common history of bioethics and corporate social responsibility and identifies their common features and differences. It then explores the dispute of jurisdictions due to professional and academic “pedigree” and incompatibilities in the ideological and teleological spheres as possible causes for the divide. The discussion turns to paths for improving the reflexivity of both disciplines and, therefore, their openness to mutual contributions. I. Cut Out of the Same Cloth The earliest record of the word “bioethics” dates back to 1927 as a term that designates one’s ethical responsibility toward not only human beings but other lifeforms as well, such as animals and plants.[1] Based on Kantian ethics, the term was coined as a response to the great prestige science held at its time. It remained largely forgotten until the 1970s, when it resurfaced in the United States[2] as the body of knowledge that can be employed to ensure the responsible pursuit and application of science. The resurgence was prompted by a response to widespread irresponsible attitudes toward science and grounded in a pluralistic perspective of morality.[3] In the second half of the twentieth century, states and the international community assumed the duty to protect human rights, and bioethics became a venue for discussing rights.[4] There is both a semantic gap and a contextual gap between these two iterations, with some of them already being established. Corporate social responsibility is often attributed to the Berle-Dodd debate. The discussion was characterized by diverging views on the extent of the responsibility of managers.[5] It was later settled as positioning the company, especially the large firm, as an entity whose existence is fomented by the law due to its service to the community. The concept has evolved with time, departing from a largely philanthropic meaning to being ingrained in nearly every aspect of a company’s operations. This includes investments, entrepreneurship models, and its relationship to stakeholders, leading to an increasing operationalization and globalization of the concept.[6] At first sight, these two movements seem to stem from different contexts. Despite the difference, it is also possible to tell a joint history of bioethics and CSR, with their point of contact being a generalized concern with technological and social changes that surfaced in the sixties. The publishing of Silent Spring in 1962 by Rachel Carson exemplifies this growing concern over the sustainability of the ruling economic growth model of its time by commenting on the effects of large-scale agriculture and the use of pesticides in the population of bees, one of the most relevant pollinators of crops consumed by humans. The book influenced both the author responsible for the coining bioethics in the 1971[7] and early CSR literature.[8] By initiating a debate over the sustainability of economic models, the environmentalist discourse became a precursor to vigorous social movements for civil rights. Bioethics was part of the trend as it would be carried forward by movements such as feminism and the patients’ rights movement.[9] Bioethics would gradually move from a public discourse centered around the responsible use of science and technology to academic and government spaces.[10] This evolution led to an increasing emphasis on intellectual rigor and governance. The transformation would unravel the effort to take effective action against scandal and turn bioethical discourse into governance practices,[11] such as bioethics and research ethics committees. The publication of the Belmont Report[12] in the aftermath of the Tuskegee Syphilis Experiment, as well as the creation of committees such as the “God Committee,”[13] which aimed to develop and enforce criteria for allocating scarce dialysis machines, exemplify this shift. On the side of CSR, this period represents, at first, a stronger pact between businesses and society due to more stringent environmental and consumer regulations. But afterward, a joint trend emerged: on one side, the deregulation within the context of neoliberalism, and on the other, the operationalization of corporate social responsibility as a response to societal concerns.[14] The 1990s saw both opportunities and crises that derived from globalization. In the political arena, the end of the Cold War led to an impasse in the discourse concerning human rights,[15] which previously had been split between the defense of civil and political rights on one side and social rights on the other. But at the same time, agendas that were previously restricted territorially became institutionalized on a global scale.[16] Events such as the European Environment Agency (1990), ECO92 in Rio de Janeiro (1992), and the UN Global Compact (2000) are some examples of the globalization of CSR. This process of institutionalization would also mirror a crisis in CSR, given that its voluntarist core would be deemed lackluster due to the lack of corporate accountability. The business and human rights movement sought to produce new binding instruments – usually state-based – that could ensure that businesses would comply with their duties to respect human rights.[17] This rule-creation process has been called legalization: a shift from business standards to norms of varying degrees of obligation, precision, and delegation.[18] Bioethics has also experienced its own renewed identity in the developed world, perhaps because of its reconnection to public and global health. Global health has been the object of study for centuries under other labels (e.g., the use of tropical medicine to assist colonial expeditions) but it resurfaced in the political agenda recently after the pandemics of AIDS and respiratory diseases.[19] Bioethics has been accused from the inside of ignoring matters beyond the patient-provider relationship,[20] including those related to public health and/or governance. Meanwhile, scholars claimed the need to expand the discourse to global health.[21] In some countries, bioethics developed a tight relationship with public health, such as Brazil,[22] due to its connections to the sanitary reform movement. The United Kingdom has also followed a different path, prioritizing governance practices and the use of pre-established institutions in a more community-oriented approach.[23] The Universal Declaration on Bioethics and Rights followed this shift toward a social dimension of bioethics despite being subject to criticism due to its human rights-based approach in a field characterized by ethical pluralism.[24] This scenario suggests bioethics and CSR have developed out of similar concerns: the protection of human rights and concerns over responsible development – be it economic, scientific, or technological. However, the interaction between these two fields (as well as business and human rights) is fairly recent both in academic and business settings. There might be a divide between these fields and their practitioners. II. A Tale of Jurisdictions It can be argued that CSR and business and human rights did not face jurisdictional disputes. These fields owe much of their longevity to their roots in institutional economics, whose debates, such as the Berle-Dodd debate, were based on interdisciplinary dialogue and the abandonment of sectorial divisions and public-private dichotomies.[25] There was opposition to this approach to the role of companies in society that could have implications for CSR’s interdisciplinarity, such as the understanding that corporate activities should be restricted to profit maximization.[26] Yet, those were often oppositions to CSR or business and human rights themselves. The birth of bioethics in the USA can be traced back to jurisdictional disputes over the realm of medicine and life sciences.[27] The dispute unfolded between representatives of science and those of “society’s conscience,” whether through bioethics as a form of applied ethics or other areas of knowledge such as theology.[28] Amid the civil rights movements, outsiders would gain access to the social sphere of medicine, simultaneously bringing it to the public debate and emphasizing the decision-making process as the center of the medical practice.[29] This led to the emergence of the bioethicist as a professional whose background in philosophy, theology, or social sciences deemed the bioethicist qualified to speak on behalf of the social consciousness. In other locations this interaction would play out differently: whether as an investigation of philosophically implied issues, a communal effort with professional institutions to enhance decision-making capability, or a concern with access to healthcare.[30] In these situations, the emergence and regulation of bioethics would be way less rooted in disputes over jurisdictions. This contentious birth of bioethics would have several implications, most related to where the bioethicist belongs. After the civil rights movements subsided, bioethics moved from the public sphere into an ivory tower: intellectual, secular, and isolated. The scope of the bioethicist would be increasingly limited to the spaces of academia and hospitals, where it would be narrowed to the clinical environment.[31] This would become the comfort zone of professionals, much to the detriment of social concerns. This scenario was convenient to social groups that sought to affirm their protagonism in the public arena, with conservative and progressive movements alike questioning the legitimacy of bioethics in the political discourse.[32] Even within the walls of hospitals and clinics, bioethics would not be excused from criticism. Afterall, the work of bioethicists is often unregulated and lacks the same kind of accountability that doctors and lawyers have. Then, is there a role to be played by the bioethicist? This trend of isolation leads to a plausible explanation for why bioethics did not develop an extensive collaboration with corporate social responsibility nor with business and human rights. Despite stemming from similar agendas, bioethics’ orientation towards the private sphere resulted in a limited perspective on the broader implications of its decisions. This existential crisis of the discipline led to a re-evaluation of its nature and purpose. Its relevance has been reaffirmed due to the epistemic advantage of philosophy when engaging normative issues. Proper training enables the bioethicist to avoid falling into traps of subjectivism or moralism, which are unable to address the complexity of decision-making. It also prevents the naïve seduction of “scientifying” ethics.[33] This is the starting point of a multitude of roles that can be attributed to the bioethicists. There are three main responsibilities that fall under bioethics: (i) activism in biopolicy, through the engagement in the creation of laws, jurisprudence, and public policies; (ii) the exercise of bioethics expertise, be it through the specialized knowledge in philosophical thought, its ability to juggle multiple languages related to various disciplines related to bioethics, or its capacity to combat and avoid misinformation and epistemic distortion; (iii) and, intellectual exchange, by exercising awareness that it is necessary to work with specialists from different backgrounds to achieve its goals.[34] All of those suggest the need for bioethics to improve its dialogue with CSR and business and human rights. Both CSR and business and human rights have been the arena of political disputes over the role of regulations and corporations themselves, and the absence of strong stances by bioethicists risks deepening their exclusion from the public arena. Furthermore, CSR and business and human rights are at the forefront of contemporary issues, such as the limits to sustainable development and appropriate governance structures, which may lead to the acceptance of values and accomplishment of goals cherished by bioethics. However, a gap in identifying the role and nature of bioethics and CSR may also be an obstacle for bridging the chasm between bioethics and CSR. III. From Substance to Form: Philosophical Groundings of CSR and Bioethics As mentioned earlier, CSR is, to some extent, a byproduct of institutionalism. Institutional economics has a philosophical footprint in the pragmatic tradition[35], which has implications for the purpose of the movement and the typical course of the debate. The effectiveness of regulatory measures is often at the center of CSR and business and human rights debates: whatever the regulatory proposal may be, compliance, feasibility, and effectiveness are the kernel of the discussion. The axiological foundation is often the protection of human rights. But discussions over the prioritization of some human rights over others or the specific characteristics of the community to be protected are often neglected.[36] It is worth reinforcing that adopting human rights as an ethical standard presents problems to bioethics, given its grounding in the recognition of ethical pluralism. Pragmatism adopts an anti-essentialist view, arguing that concepts derive from their practical consequences instead of aprioristic elements.[37] Therefore, truth is transitory and context dependent. Pragmatism embraces a form of moral relativism and may find itself in an impasse in the context of political economy and policymaking due to its tendency to be stuck between the preservation of the status quo and the defense of a technocratic perspective, which sees technical and scientific progress as the solution to many of society’s issues.[38] These characteristics mean that bioethics has a complicated relationship with pragmatism. Indeed, there are connections between pragmatism and the bioethics discourse. Both can be traced back to American naturalism.[39] The early effort in bioethics to make it ecumenical, thus building on a common but transitory morality,[40] sounds pragmatic. Therefore, scholars suggest that bioethics should rely on pragmatism's perks and characteristics to develop solutions to new ethical challenges that emerge from scientific and technological progress. Nonetheless, ethical relativism is a problem for bioethics when it bleeds from a metaethical level into the subject matters themselves. After all, the whole point of bioethics is either descriptive, where it seeks to understand social values and conditions that pertain to its scope, or normative, where it investigates what should be done in matters related to medicine, life sciences, and social and technological change. It is a “knowledge of how to use knowledge.” Therefore, bioethics is a product of disillusionment regarding science and technology's capacity to produce exclusively good consequences. It was built around an opposition to ethical relativism—even though the field is aware of the particularity of its answers. This is true not only for the scholarly arena, where the objective is to produce ethically sound answers but also for bioethics governance, where relativism may induce decision paralysis or open the way to points of view disconnected from facts.[41] But there might be a point for more pragmatic bioethics. Bioethics has become an increasingly public enterprise which seeks political persuasion and impact in the regulatory sphere. When bioethics is seen as an enterprise, achieving social transformation is its main goal. In this sense, pragmatism can provide critical tools to identify idiosyncrasies in regulation that prove change is needed. An example of how this may play out is the abortion rights movement in the global south.[42] Despite barriers to accessing safe abortion, this movement came up with creative solutions and a public discourse focused on the consequences of its criminalization rather than its moral aspects. IV. Bridging the Divide: Connections Between Bioethics and CSR There have been attempts to bring bioethics and CSR closer to each other. Corporate responsibility can be a supplementary strategy for achieving the goals of bioethics. The International Bioethics Committee (IBC), an institution of the United Nations Educational, Scientific and Cultural Organization (UNESCO), highlights the concept that social responsibility regarding health falls under the provisions of the Universal Declaration on Bioethics and Human Rights (UDBHR). It is a means of achieving good health (complete physical, mental, and social well-being) through social development.[43] Thus, it plays out as a condition for actualizing the goals dear to bioethics and general ethical standards,[44] such as autonomy and awareness of the social consequences of an organization’s governance. On this same note, CSR is a complementary resource for healthcare organizations that already have embedded bioethics into their operations[45] as a way of looking at the social impact of their practices. And bioethics is also an asset of CSR. Bioethics can inform the necessary conditions for healthcare institutions achieving a positive social impact. When taken at face value, bioethics may offer guidelines for ethical and socially responsible behavior in the industry, instructing how these should play out in a particular context such as in research, and access to health.[46] When considering the relevance of rewarding mechanisms,[47] bioethics can guide the establishment of certification measures to restore lost trust in the pharmaceutical sector.[48] Furthermore, recognizing that the choice is a more complex matter than the maximization of utility can offer a nuanced perspective on how organizations dealing with existentially relevant choices understand their stakeholders.[49] However, all of those proposals might come with the challenge of proving that something can be gained from its addition to self-regulatory practices[50] within the scope of a dominant rights-based approach to CSR and global and corporate law. It is evident that there is room for further collaboration between bioethics and CSR. Embedding either into the corporate governance practices of an organization tends to be connected to promoting the other.[51] While there are some incompatibilities, organizations should try to overcome them and take advantage of the synergies and similarities. CONCLUSION Despite their common interests and shared history, bioethics and corporate social responsibility have not produced a mature exchange. Jurisdictional issues and foundational incompatibilities have prevented a joint effort to establish a model of social responsibility that addresses issues particular to the healthcare sector. Both bioethics and CSR should acknowledge that they hold two different pieces of a cognitive competence necessary for that task: CSR offers experience on how to turn corporate ethical obligations operational, while bioethics provides access to the prevailing practical and philosophical problem-solving tools in healthcare that were born out of social movements. Reconciling bioethics and CSR calls for greater efforts to comprehend and incorporate the social knowledge developed by each field reflexively[52] while understanding their insights are relevant to achieving some common goals. - [1]. Fritz Jahr, “Bio-Ethik: Eine Umschau Über Die Ethischen Beziehungen Des Menschen Zu Tier Und Pflanze,” Kosmos - Handweiser Für Naturfreunde 24 (1927): 2–4. [2]. Van Rensselaer Potter, “Bioethics, the Science of Survival,” Perspectives in Biology and Medicine 14, no. 1 (1970): 127–53, https://doi.org/10.1353/pbm.1970.0015. [3]. Maximilian Schochow and Jonas Grygier, eds., “Tagungsbericht: 1927 – Die Geburt der Bioethik in Halle (Saale) durch den protestantischen Theologen Fritz Jahr (1895-1953),” Jahrbuch für Recht und Ethik / Annual Review of Law and Ethics 21 (June 11, 2014): 325–29, https://doi.org/10.3726/978-3-653-02807-2. [4] George J. Annas, American Bioethics: Crossing Human Rights and Health Law Boundaries (Oxford ; New York: Oxford University Press, 2005). [5] Philip L. Cochran, “The Evolution of Corporate Social Responsibility,” Business Horizons 50, no. 6 (November 2007): 449–54, https://doi.org/10.1016/j.bushor.2007.06.004. p. 449. [6] Mauricio Andrés Latapí Agudelo, Lára Jóhannsdóttir, and Brynhildur Davídsdóttir, “A Literature Review of the History and Evolution of Corporate Social Responsibility,” International Journal of Corporate Social Responsibility 4, no. 1 (December 2019): 23, https://doi.org/10.1186/s40991-018-0039-y. [7] Potter, “Bioethics, the Science of Survival.” p. 129. [8] Latapí Agudelo, Jóhannsdóttir, and Davídsdóttir, “A Literature Review of the History and Evolution of Corporate Social Responsibility.” p. 4. [9] Albert R. Jonsen, The Birth of Bioethics (New York: Oxford University Press, 2003). p. 368-371. [10] Jonsen. p. 372. [11] Jonathan Montgomery, “Bioethics as a Governance Practice,” Health Care Analysis 24, no. 1 (March 2016): 3–23, https://doi.org/10.1007/s10728-015-0310-2. [12]. The National Commission for the Protection of Human Subjects of Biomedical and Behavioral Research, “The Belmont Report: Ethical Principles and Guidelines for the Protection of Human Subjects of Research” (Washington: Department of Health, Education, and Welfare, April 18, 1979), https://www.hhs.gov/ohrp/sites/default/files/the-belmont-report-508c_FINAL.pdf. [13] Shana Alexander, “They Decide Who Lives, Who Dies,” in LIFE, by Time Inc, 19th ed., vol. 53 (Nova Iorque: Time Inc, 1962), 102–25. [14]. Latapí Agudelo, Jóhannsdóttir, and Davídsdóttir, “A Literature Review of the History and Evolution of Corporate Social Responsibility.” [15]. Boaventura de Sousa Santos, “Por Uma Concepção Multicultural Dos Direitos Humanos,” Revista Crítica de Ciências Sociais, no. 48 (June 1997): 11–32. [16] Latapí Agudelo, Jóhannsdóttir, and Davídsdóttir, “A Literature Review of the History and Evolution of Corporate Social Responsibility.” [17]. Anita Ramasastry, “Corporate Social Responsibility Versus Business and Human Rights: Bridging the Gap Between Responsibility and Accountability,” Journal of Human Rights 14, no. 2 (April 3, 2015): 237–59, https://doi.org/10.1080/14754835.2015.1037953. [18]. Kenneth W Abbott et al., “The Concept of Legalization,” International Organization, Legalization and World Politics, 54, no. 3 (2000): 401–4019. [19]. Jens Holst, “Global Health – Emergence, Hegemonic Trends and Biomedical Reductionism,” Globalization and Health 16, no. 1 (December 2020): 42–52, https://doi.org/10.1186/s12992-020-00573-4. [20]. Albert R. Jonsen, “Social Responsibilities of Bioethics,” Journal of Urban Health: Bulletin of the New York Academy of Medicine 78, no. 1 (March 1, 2001): 21–28, https://doi.org/10.1093/jurban/78.1.21. [21]. Solomon R Benatar, Abdallah S Daar, and Peter A Singer, “Global Health Challenges: The Need for an Expanded Discourse on Bioethics,” PLoS Medicine 2, no. 7 (July 26, 2005): e143, https://doi.org/10.1371/journal.pmed.0020143. [22]. Márcio Fabri dos Anjos and José Eduardo de Siqueira, eds., Bioética No Brasil: Tendências e Perspectivas, 1st ed., Bio & Ética (São Paulo: Sociedade Brasileira de Bioética, 2007). [23]. Montgomery, “Bioethics as a Governance Practice.” p. 8-9. [24]. Aline Albuquerque S. de Oliveira, “A Declaração Universal Sobre Bioética e Direitos Humanos e a Análise de Sua Repercussão Teórica Na Comunidade Bioética,” Revista Redbioética/UNESCO 1, no. 1 (2010): 124–39. [25] John R. Commons, “Law and Economics,” The Yale Law Journal 34, no. 4 (February 1925): 371, https://doi.org/10.2307/788562; Robert L. Hale, “Bargaining, Duress, and Economic Liberty,” Columbia Law Review 43, no. 5 (July 1943): 603–28, https://doi.org/10.2307/1117229; Karl N. Llewellyn, “The Effect of Legal Institutions Upon Economics,” The American Economic Review 15, no. 4 (1925): 665–83; Carlos Portugal Gouvêa, Análise Dos Custos Da Desigualdade: Efeitos Institucionais Do Círculo Vicioso de Desigualdade e Corrupção, 1st ed. (São Paulo: Quartier Latin, 2021). p. 84-94. [26] Milton Friedman, “A Friedman Doctrine‐- The Social Responsibility of Business Is to Increase Its Profits,” The New York Times, September 13, 1970, sec. Archives, https://www.nytimes.com/1970/09/13/archives/a-friedman-doctrine-the-social-responsibility-of-business-is-to.html. [27] Montgomery, “Bioethics as a Governance Practice.” p. 8. [28] John Hyde Evans, The History and Future of Bioethics: A Sociological View, 1st ed. (New York: Oxford University Press, 2012). [29] David J. Rothman, Strangers at the Bedside: A History of How Law and Bioethics Transformed Medical Decision Making, 2nd pbk. ed, Social Institutions and Social Change (New York: Aldine de Gruyter, 2003). p. 3. [30] Volnei Garrafa, Thiago Rocha Da Cunha, and Camilo Manchola, “Access to Healthcare: A Central Question within Brazilian Bioethics,” Cambridge Quarterly of Healthcare Ethics 27, no. 3 (July 2018): 431–39, https://doi.org/10.1017/S0963180117000810. [31] Jonsen, “Social Responsibilities of Bioethics.” [32] Evans, The History and Future of Bioethics. p. 75-79, 94-96. [33] Julian Savulescu, “Bioethics: Why Philosophy Is Essential for Progress,” Journal of Medical Ethics 41, no. 1 (January 2015): 28–33, https://doi.org/10.1136/medethics-2014-102284. [34] Silvia Camporesi and Giulia Cavaliere, “Can Bioethics Be an Honest Way of Making a Living? A Reflection on Normativity, Governance and Expertise,” Journal of Medical Ethics 47, no. 3 (March 2021): 159–63, https://doi.org/10.1136/medethics-2019-105954; Jackie Leach Scully, “The Responsibilities of the Engaged Bioethicist: Scholar, Advocate, Activist,” Bioethics 33, no. 8 (October 2019): 872–80, https://doi.org/10.1111/bioe.12659. [35] Philip Mirowski, “The Philosophical Bases of Institutionalist Economics,” Journal of Economic Issues, Evolutionary Economics I: Foundations of Institutional Thought, 21, no. 3 (September 1987): 1001–38. [36] David Kennedy, “The International Human Rights Movement: Part of the Problem?,” Harvard Human Rights Journal 15 (2002): 101–25. [37] Richard Rorty, “Pragmatism, Relativism, and Irrationalism,” Proceedings and Addresses of the American Philosophical Association 53, no. 6 (August 1980): 717+719-738. [38]. Mirowski, “The Philosophical Bases of Institutionalist Economics.” [39]. Glenn McGee, ed., Pragmatic Bioethics, 2nd ed, Basic Bioethics (Cambridge, Mass: MIT Press, 2003). [40]. Tom L. Beauchamp and James F. Childress, Principles of Biomedical Ethics, 7th ed (New York: Oxford University Press, 2013). [41]. Montgomery, “Bioethics as a Governance Practice.” [42]. Debora Diniz and Giselle Carino, “What Can Be Learned from the Global South on Abortion and How We Can Learn?,” Developing World Bioethics 23, no. 1 (March 2023): 3–4, https://doi.org/10.1111/dewb.12385. [43]. International Bioethics Committee, On Social Responsibility and Health Report (Paris: Unesco, 2010). [44]. Cristina Brandão et al., “Social Responsibility: A New Paradigm of Hospital Governance?,” Health Care Analysis 21, no. 4 (December 2013): 390–402, https://doi.org/10.1007/s10728-012-0206-3. [45] Intissar Haddiya, Taha Janfi, and Mohamed Guedira, “Application of the Concepts of Social Responsibility, Sustainability, and Ethics to Healthcare Organizations,” Risk Management and Healthcare Policy Volume 13 (August 2020): 1029–33, https://doi.org/10.2147/RMHP.S258984. [46]The Biopharmaceutical Bioethics Working Group et al., “Considerations for Applying Bioethics Norms to a Biopharmaceutical Industry Setting,” BMC Medical Ethics 22, no. 1 (December 2021): 31–41, https://doi.org/10.1186/s12910-021-00600-y. [47] Anne Van Aaken and Betül Simsek, “Rewarding in International Law,” American Journal of International Law 115, no. 2 (April 2021): 195–241, https://doi.org/10.1017/ajil.2021.2. [48] Jennifer E. Miller, “Bioethical Accreditation or Rating Needed to Restore Trust in Pharma,” Nature Medicine 19, no. 3 (March 2013): 261–261, https://doi.org/10.1038/nm0313-261. [49] John Hardwig, “The Stockholder – A Lesson for Business Ethics from Bioethics?,” Journal of Business Ethics 91, no. 3 (February 2010): 329–41, https://doi.org/10.1007/s10551-009-0086-0. [50] Stefan van Uden, “Taking up Bioethical Responsibility?: The Role of Global Bioethics in the Social Responsibility of Pharmaceutical Corporations Operating